JPEG movie over Zigbee mesh - David, Arianne T.; Dogillo, Karen Maye S.; Pingca, kenneth John C.; Tedor, Anna Rizza T. (2009)
ZigBee, over IEEE 802.15.4, is a standard wireless protocol for short-range wireless communications. ZigBee provides low data rate and is very suitable for applications with limited battery life. The project creates a wireless network that transmits images over ZigBee mesh. The captured images are transmitted to the main station by using image-to-video converter software. The end device, composed of a ZigBee module interfaced with a camera and an external Real Time Clock, is powered by a supply using a solar panel and a battery. A antenna is used to achieve longer transmission range. The project can be a very efficient security system if developed further. It can be deployed in both small and big establishments to monitor malicious acts. This flexible and practical application of ZigBee can be made comparable to the present technology.
Thesis (B.S Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Wireless LANs -- Standards; JPEG (Image coding standard); Zigbee; JPEG movie